Effect of Spraying Aizomen, Sunflower Leaves Extract and Cutting on Growth and Content of Some Phytoconstituents on Leaves and Seeds of Rocket - Al-Mohammad, Maher H.S.; Al-Kikhani, Ali H.J (Journal of Kerbala for Agricultural Sciences, 2018)
This field experiment was conducted during the growing season of 2016/2017 to study the effect of spraying Aizomen, Sunflower extracts, Cutting and their combination treatments on growth parameters and some phytoconstituents compounds of Rocket Eruca sativa Mill., The treatments were distributed on Randomized Completely Block Design in three replicates, means were compared according to the Least Significant Difference test at probability level of 0.05 and t-test for comparing between cutting. The results show the sprayed 1.5 ml.L-1 Aizomen + 2% Extract gave the highest means on growth parameters (leaves number, fresh and dry weight and leaves productivity) at 1st and 2st cut and seeds productivity, at the same time it was increased the content of leaves and seeds of total alkaloids. While the treat 1.5 ml.L-1 Aizomen + 4% Extract was gave significant difference on concentrations of some phytoconstituents compounds Phenols, Flavonoids Tannins and Saponins compounds which amounted on leaves to 11.95, 3.38, 1.52 and 0.72 at 1st cut, 15.91, 4.18, 1.66 and 0.79 at 2st cut and on seeds reached 41.68, 11.35, 4.88 and 2.28 mg.g-1D.W respectively.